Research Trend of Marine Engineering in India and China during 2010-2019 - Jilani, Gulam; Banerjee, Swapna (Qualitative and Quantitative Methods in Libraries, 2021)
The study aims to present a comparative scientometric analysis of the research trend of marine engineering in India and China from 2010 to 2019. In this study, 2909 publications of China and 585 publications of India from various sources were collected and analyzed. This scientometric study covers year-wise publication, preference of documents type, authorship pattern, author h-index, citation analysis, keyword analysis, and collaboration of both countries with others. The data has been extracted from the SCOPUS database for both countries China and India separately with limitations up to ten years. Document type of article is very popular in both countries and authors prefer to get published in journals. A number of results have cropped in through this study, which has been depicted through diagrams and tables here.